ANALISIS PENDAPATAN PETANI JERUK SIAM (Citrus nobilis lour) DI DESA KUOK KECAMATAN KUOK KABUPATEN KAMPAR - Herdian Eka Saputra; Ermi Tety; Eliza Eliza (Indonesian Journal of Agricultural Economics, 2017)
The purpose of this research was to determine the use of cost, income, and the level of efficiency value of siam orange farming in Kuok village, Kuok sub-district, Kampar district. Sampling method used purposive sampling method which that  to criticize based on land area and age of plant. Methods of data collection is done by observation, interview and documentation. The data analysis technique used to calculate the income and the level of efficiency value of siam orange farming using R/C Ratio analysis tool. The results showed the total cost, income and profits of the siam orange farming and rice income. Total cost production of siam orange is  IDR 474.558.333,33/year with average cost production each respondent is IDR 23.727.916,67/0.58ha/year. Total income of siam orange is IDR 1.082.510.000,00/year with average income each respondent is IDR 54.125.500,00/0.58ha/year. The value of R/C Ratio from siam orange farming is 2,28 so that farming is capable to cultivate.